Foetal well-being in primigravid patients in a multicultural community - Lester, Barbara-Ann (My University, 2014)
The introduction of free mother and child services in South Africa in 1994, changed the way in which the services were delivered. There was an increase in the number of women seeking services, therefore a need arose to look at what constituted essential, basic services. The introduction of the maternal held card in State hospitals enabled the women to seek ante-natal care at the venue most accessible to her. This document also involved her in the responsibility of her own care and that of her unborn child. This study explored the information which mothers had been given ante-natally to assist them with the task of bearing the responsibility of their unborn child's health, which they had unilaterally been given by the Healthcare providers. A descriptive study was undertaken and 221 primigravid patients were interviewed at a large academic hospital post-delivery using a structured interview schedule. Their records were also reviewed retrospectively for type of delivery and foetal outcome. Results of the studies found that the mothers were given insufficient information to equip them with responsibility of assessing foetal health. Healthcare providers, it was found, did not give specific information and it appeared that at times, the mothers report of decreased foetal movement was disregarded. Implications of the study are that healthcare providers need to pay attention to how they provide information. The women interviewed clearly made the distinction between what was seen as 'teaching' and what was perceived as information given. It is also important to note that although the health workers understand the implications of foetal well-being, patients do not necessarily share the same insight or sense of responsibility. This has implications for the delivery of antenatal services in South Africa.
Keywords: Fetal Monitoring; Fetal Movement